APPLICATION OF ROLE PLAYING LEARNING METHODS TO IMPROVE SELF-CONFIDENCE AND SPEAKING SKILLS (Study in English Lessons for Class XI SMAN 1 Students West Merapi) - Nurtina Nurtina; Johanes Sapri (UNIB Press, 2019)
The purpose of this study was to describe the application and the effectiveness of role playing learning method in improving student’s confidence and achievment on speaking af the grade XI at SMA Negeri 1 Merapi Barat. The research method was classroom action research and quasi experimental. The research subject were students of the grade XI IPA 3 term one of the 2019/2020 school year. The quasi experimental sample were the grade XI IPA 1 and XI IPA 2, sampling taking by purposive sampling. The data collection techniques used the observation sheets. The data analysis used t-test The conclusion was that the application of role playing method can improve students’ confidence and speaking skill